2014
DOI: 10.1097/inf.0000000000000353
|View full text |Cite
|
Sign up to set email alerts
|

Performance of interferon-γ Release Assay for the Diagnosis of Active or Latent Tuberculosis in Children in the First 2 Years of Age

Abstract: QTF-IT showed good sensitivity and specificity, and a low rate of indeterminate results in the first 2 years of life, supporting its use at this age. However, considering costs and the similar performance between QTF-IT and TST, it is reasonable to suggest the latter as first-line testing in young children. The complementary use of TST and interferon-γ release assays may be considered in selected cases to improve the accuracy of testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 29 publications
5
17
0
Order By: Relevance
“…Results have been conflicting at times, with some studies showing comparable sensitivity and specificity to TST, whereas others found higher or lower sensitivity. 3,[26][27][28][29][30][31][32] Rates of indeterminate QFT tests have been higher in young children than in adults; 26,[33][34][35][36] although in this study, we noted a low rate of indeterminate tests (0·4% of all tests).…”
Section: Discussionmentioning
confidence: 39%
“…Results have been conflicting at times, with some studies showing comparable sensitivity and specificity to TST, whereas others found higher or lower sensitivity. 3,[26][27][28][29][30][31][32] Rates of indeterminate QFT tests have been higher in young children than in adults; 26,[33][34][35][36] although in this study, we noted a low rate of indeterminate tests (0·4% of all tests).…”
Section: Discussionmentioning
confidence: 39%
“…Evaluation of IGRA performance in children remains limited due to small study sizes, resistance to phlebotomy, and difficulty in obtaining culture-confirmed results for reference (32). Sensitivity and specificity have been assessed in studies using either culture-confirmed cases or an exposure gradient as a surrogate for infection, but outcomes as well as proportion of indeterminate results are discordant, particularly in infants under 5 years (19,20,33,34). In our previous report, we showed good sensitivity (93.3%) and specificity (99.3%) of QFT-IT in comparison with TST for diagnosis of active TB (23).…”
Section: Discussionmentioning
confidence: 99%
“…35 Prior guidelines have recommended the TST in children younger than 5 years of age, but increasingly the IGRA are being preferred in children of all ages who have likely been BCG vaccinated. 35 Studies which found comparable sensitivity and superior specificity of the QFT-GIT as compared with the TST, [36][37][38] as well as a longitudinal study of QFT-GIT conversions 39 are providing helpful data to guide care. Children younger than 2 years of age are at particularly high risk of progression to active TB.…”
Section: Guidelines For Use Of Tst/igra For Ltbi Testingmentioning
confidence: 99%